The plasticity of the superior longitudinal fasciculus as a function of musical expertise: a diffusion tensor imaging study - Oechslin, Mathias S.; Imfeld, Adrian; Loenneker, Thomas; Meyer, Martin; Jäncke, Lutz (Frontiers in Human Neuroscience, 2010)
Previous neuroimaging studies have demonstrated that musical expertise leads to functional alterations in language processing. We utilized diffusion tensor imaging (DTI) to investigate white matter plasticity in musicians with absolute pitch (AP), relative pitch (RP) and non-musicians (NM). Using diffusion tensor imaging (DTI), we analyzed the fractional anisotropy of the superior longitudinal fasciculus (SLF), which is considered the most primary pathway for processing and production of speech and music. In association with different levels of musical expertise, we found that AP is characterized by a greater left than right asymmetry of fractional anisotropy (FA) in core fibres of the SLF. A voxel-based analysis revealed three clusters within the left hemisphere SLF that showed significant positive correlations with error rates only for AP-musicians in an AP-test, but not for musicians without AP. We therefore conclude that the SLF architecture in AP musicians is related to AP acuity. In order to reconcile our observations with general aspects of development of fibre bundles, we introduce the Pioneer Axon Thesis, a theoretical approach to formalize axonal arrangements of major white matter pathways.